Risk factors for pediatric intoxications in the prehospital setting. A geospatial survey - Kienbacher, Calvin Lukas; Wei, Guixing; Rhodes, Jason M.; Herkner, Harald; Roth, Dominik; Williams, Kenneth A. (Frontiers in Public Health, 2024)
Background Socioeconomic factors and the COVID-19 pandemic influence children’s physical and mental health. We aimed to investigate the association between a census tract’s median household income [MHI in United States Dollars ($)] and pediatric intoxications in Rhode Island, the smallest state in the United States of America. Geographical hotspots, as well as interactions with the COVID-19 pandemic, should be identified. Methods This study is a retrospective analysis of ambulance calls for pediatric (<18 years) intoxication in Rhode Island between March 1st, 2018, and February 28th, 2022. March 1st, 2020 was considered the beginning of the COVID-19 pandemic. Prehospital data were joined with information from the United States Census Bureau. The census tracts’ case counts and MHI were examined using Poisson regression. Geographical clusters were identified with the Global Moran’s I and local indicators of spatial association tests in ArcGIS Pro (Esri Corporation, Redlands, CA). Results Inclusion criteria were met by 208 incidents (48% female, median age 16 (IQR 15 to 17) years). The regression model showed a 0.6% increase (IRR 1.006, 95% CI [1.002, 1.01], p = 0.003) in pediatric intoxications for every $ 1,000 increase in MHI. Interaction analysis showed that the effect of MHI was less pronounced during the pandemic (IRR 0.98, 95% CI [0.964, 0.997], p = 0.02). Thirty-four (14%) of the 244 census tracts contributed to geographical clusters, which changed after the onset of the pandemic. Conclusion Higher median household income could be a risk factor for pediatric intoxications. Geographical hotspots changed with the pandemic.